Optimizing Tax Apparatus Performance Management in Implementing a Modern Tax Administration System - Paroli, Paroli (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
Taxes play a vital role in overseeing state finances, and enhancing the performance management of tax officials is essential for achieving the efficiency and long-term viability of the tax system. This research aims to examine and determine the most effective approaches to managing the performance of the tax apparatus, particularly in implementing a contemporary tax administration system. This study employs a qualitative methodology utilizing descriptive techniques. The research findings indicate that implementing tax administration reform in Indonesia, mainly through using advanced information and communication technology such as e-registration, e-filing, and e-billing, has resulted in a favorable outcome by enhancing efficiency, responsiveness, and transparency in tax management. These measures facilitate endeavors to enhance taxpayer adherence and bolster tax revenues. In addition, enhancing the performance management of the Tax Apparatus, particularly Account Representatives, in implementing a contemporary tax administration system entail employing crucial tactics such as ongoing training, utilization of specific performance metrics, and integration of information technology such as CRM. Providing rewards and professional growth chances for strong performance can enhance motivation while implementing open feedback methods and constant review can serve as a foundation for improvement. Cultivating interpersonal skills is equally crucial for enhancing connections with taxpayers. Continuous monitoring ensures that performance management techniques stay up-to-date and adaptable to changes in the tax environment. This helps achieve optimal tax revenue goals and enhances taxpayer compliance within the framework of modern tax administration.